2007
DOI: 10.1007/s10532-007-9143-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the microbial diversity in a horizontal-flow anaerobic immobilized biomass reactor treating linear alkylbenzene sulfonate

Abstract: The purpose of this work was to assess the degradation of linear alkylbenzene sulfonate (LAS) in a horizontal-flow anaerobic immobilized biomass (HAIB) reactor. The reactor was filled with polyurethane foam where the sludge from a sanitary sewage treatment was immobilized. The hydraulic detention time (HDT) used in the experiments was of 12 h. The reactor was fed with synthetic substrate (410 mg l(-1) of meat extract, 115 mg l(-1) of starch, 80 mg l(-1) of saccharose, 320 mg l(-1) of sodium bicarbonate and 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
16

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 30 publications
1
20
0
16
Order By: Relevance
“…Oliveira et al (2009) and Duarte et al (2008) obtained removal efficiencies of 28% and 35%, respectively, in a horizontal anaerobic immobilized biomass reactor (HAIB). In a UASB reactor with 4 mg.L -1 of LAS influent, Sanz et al (2003) found removal of 85%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oliveira et al (2009) and Duarte et al (2008) obtained removal efficiencies of 28% and 35%, respectively, in a horizontal anaerobic immobilized biomass reactor (HAIB). In a UASB reactor with 4 mg.L -1 of LAS influent, Sanz et al (2003) found removal of 85%.…”
Section: Resultsmentioning
confidence: 99%
“…In a UASB reactor with 4 mg.L -1 of LAS influent, Sanz et al (2003) found removal of 85%. The efficiencies achieved in the work of Oliveira et al (2009) and Duarte et al (2008), in addition to degradation, consider the LAS removed by adsorption on the support. However, in this work with the fluidized bed reactor, degradation was therefore obtained without the adsorption of LAS onto biomass and sand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for anaerobic systems, information is scarce and has been reported only recently, mainly due to recalcitrance of LAS in those systems. Removal efficiency of about 35% was achieved in horizontal anaerobic fixed bed (Duarte et al, 2008), and 85% in Upflow Anaerobic Sludge Blanket (UASB) reactors (Sanz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in this area have focused on the use of UASB and fixed bed reactors (Almendariz et al, 2001;Sanz et al, 2003;Duarte et al 2008, Oliveira et al 2009). The microbial communities from biomass present in the reactor were described by 16S rRNA gene analysis.…”
Section: Introductionmentioning
confidence: 99%